Carbon Nanotube-Induced Pulmonary Granulomatous Disease: 1 and Alveolar Macrophage M1 Activation - Barna, Barbara P.; Huizar, Isham; Malur, Anagha; McPeek, Matthew; Marshall, Irene; Jacob, Mark; Dobbs, Larry; Kavuru, Mani S.; Thomassen, Mary Jane (My University, 2013)
Sarcoidosis, a chronic granulomatous disease of unknown cause, has been linked to several environmental risk factors, among which are some that may favor carbon nanotube formation. Using gene array data, we initially observed that bronchoalveolar lavage (BAL) cells from sarcoidosis patients displayed elevated mRNA of the transcription factor, Twist1, among many M1-associated genes compared to healthy controls. Based on this observation we hypothesized that Twist1 mRNA and protein expression might become elevated in alveolar macrophages from animals bearing granulomas induced by carbon nanotube instillation. To address this hypothesis, wild-type and macrophage-specific peroxisome proliferator-activated receptor gamma (PPARγ) knock out mice were given oropharyngeal instillation of multiwall carbon nanotubes (MWCNT). BAL cells obtained 60 days later exhibited significantly elevated Twist1 mRNA expression in granuloma-bearing wild-type or PPARγ knock out alveolar macrophages compared to sham controls. Overall, Twist1 expression levels in PPARγ knock out mice were higher than those of wild-type. Concurrently, BAL cells obtained from sarcoidosis patients and healthy controls validated gene array data: qPCR and protein analysis showed significantly elevated Twist1 in sarcoidosis compared to healthy controls. In vitro studies of alveolar macrophages from healthy controls indicated that Twist1 was inducible by classical (M1) macrophage activation stimuli (LPS, TNFα) but not by IL-4, an inducer of alternative (M2) macrophage activation. Findings suggest that Twist1 represents a PPARγ-sensitive alveolar macrophage M1 biomarker which is induced by inflammatory granulomatous disease in the MWCNT model and in human sarcoidosis.
Keywords: Twist1; alveolar macrophages; carbon nanotubes; sarcoidosis